Implementasi Metode Rapid Application Development dalam Sistem Informasi Perhitungan Rencana Anggaran Biaya Berbasis Web - Galuh Saputri; Willis Puspita Sari; Agung Siswopranoto; Joko Suwarno (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Budget planning is very necessary for an activity, so that the activity runs well. Especially for a client who wants to know the budget for building a house or renovating a house, so that the client can prepare their financial plan. However, the current budget planning system is considered less effective because the client still has to meet and consult with the contractor developer to find out the budget for building or renovating a house. In order to solve this problem, a web-based information system was created which can later make it easier for clients to find out the budget planning (RAB) and make it easier for the staff at the contractor developer. This study uses the RAD (Rapid Application Development) method where the flow and stages used include requirement planning, RAD design workshop, implementation. The results of this study are in the form of a Budget Plan Calculation Information System (RAB) which is expected to help and make it easier for clients to predict or find out the budget for building or renovating a house and can facilitate the data processing process of the JK Home Solution contractor developer.